(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Three benzaldehyde derived Schiff-bases (SH 1-3) were synthesized by a condensation reaction from o-phenylenediamine with their respective benzaldehyde derivatives in absolute ethanolic solution under reflux reaction mixture for 6-8 hrs. The structural determinations of the synthesized Schiff-bases were confirmed by FT-IR and 1H-NMR spectroscopy. Benzaldehyde derived Schiff-bases are well-known to possess potent antioxidant and anticonvulsant activities etc. In view of the importance of various benzaldehyde derivatives, the present investigation was undertaken which deals with the structure activity relationship (SAR) study and evaluation of the antioxidant and anticonvulsant activity of synthesized Schiff-bases in mice models. Materials and Methods: DPPH scavenging activity was used to assess the antioxidant activity. Pentylenetetrazole (PTZ) seizure models were used to evaluate the anticonvulsion activity and biochemical evaluation by estimation of brain GABA level of synthesized compounds. Results: In SAR study, the results revealed that the synthesized compounds SH 3, SH 2 and SH 1 at dose of 50 mg/kg show potent pharmacological activities like antioxidant and anticonvulsant activities respectively as compared to the control group at (p<0.001). Conclusion: The significant results were showed by the synthesized compounds SH 3, SH 2 and SH 1 respectively in suitable and intermediate ranges which prompted us to study their other pharmacological activities like antiviral, antibacterial, anticancer and so on. Also, the results revealed that the synthesized compounds have some effects on benzodiazipines receptors and it might link with binding sites that altered the activity of GABA receptor complex. These observations suggested that the anticonvulsant activity of synthesized compounds could be due to the involvement of the GABAergic pathway since further studies are require to exposed the underlying mechanism in detail.